Literature Review on Detection Systems for Wild Animal Intrusions - Abraham, Aibin; Mathew, Bibin; Panikkar, Devika; John, Jaya (Journal of Soft Computing Paradigm, 2023)
Agriculture is a crucial contributor to the economy, and farmers aim to increase their crop yields annually. However, with the increasing deforestation and destruction of wildlife habitats, wild animals are venturing out of the forest in search of food and often end up in nearby agricultural fields, leading to conflicts between farmers and wildlife. To address this issue, technology can be used to detect animal intrusions. Wireless sensors and animal intrusion detection systems, equipped with object detection and segmentation, can alert farmers regarding any animal incursions on their fields even when they are not present. When an animal enters the field, cameras at various locations capture images and send them to processors for analysis. The system then sends automatic notifications with images to landowners and foresters, thus providing an early warning so that appropriate action depending on the type of intruder can be taken. The system uses feature extraction and image matching techniques, along with regression algorithms, to identify and classify the intruding animal. This survey focuses on exploring the various steps, tools, and experimental setups that can be used to prevent human-wildlife conflicts and protect lives.